Screening youth soccer players by means of cognitive function and agility testing - Lovecchio, N.; Manes, G.; Filipas, L.; Giuriato, M.; Torre, A. L.; Iaia, F. M.; Codella, R. (Perceptual and Motor Skills, 2021)
Talent identification in sports is a heavily debated topic. Previous studies have separately explored either executive functions or gross motor skills to predict the success of top-level soccer players or, more generally, to characterize elite performance in soccer. However, at mid-childhood, the possibility to scope sport-specific requirements remains elusive. We aimed in this study to investigate a valid and simple method of testing for a unique combination of cognitive and speed abilities for identifying promising soccer players at mid-childhood. We measured cognitive functions by means of a Stroop smartphone application and agility with a T-Drill Ball-success test, in two groups of (a) elite- (n = 31) and (b) low-division (n = 37) Italian 7-year-old male soccer players. We administered the tests in a randomized order to both groups. We found better inhibitory control, cognitive flexibility and soccer-specific agility in high-division versus low-division players (p < .001). Inhibitory response and agility were positively associated with the augmented quality of the performance from low-division players to high-division players (r = .55; p = .0001). These results suggest that, even at an early age, cognitive control together with soccer-specific skills is associated with better performance.